O NOME E SEUS DESAFIOS: REPRESENTAÇÕES SOCIAIS DO DIRETOR/GESTOR ESCOLAR ACERCA DO SEU AGIR PROFISSIONAL - MARANGONI, RICARDO ALEXANDRE (2017)
This study, attached to the research line “Teacher Formation” of the Post-Graduation in Education of the Metodista University of São Paulo, aimed to investigate the social representations of a group of school managers in a Public School system in the State of São Paulo about their professional act. The vast theoretical production about teaching work testifies the importance of investigating the teachers’ representations, but still they are few studies which approach the school, manager’s act, in a psychol-social perspective of the theory of social representations. In this sense, we based on it and we discussed the relationship between social-practical representations and social-experience representations. The accomplishment of this research covers two moments which interconnect: at the first, the formation of the theoretical corpus, whose approaches express what they should do, that is, the studies which deal with the school manager’s work and the legal guidelines that orientate his/her work. At the second, the data was collected through a questionnaire involving close and open issues. With the first, we knew the participants’ profile and, with the second, we have approached the social representations about their professional action. The gathering expressed what they say they do and what they say what they would like to do. Therefore, we pursued to investigate the following issues. How do they represent themselves? What represents managing a school? What are the social representations about their professional act? How are they built? The results, after the content analysis, we aimed a highly symbolic degree referred to the past, which is manifested in the ground of tensions around a role invested with meaning and sense, which are launched as a challenge. The representations of the researched managers are bound to a politically correct speech and, it was the reason that, at the end of this work, we decided to call upon the mute zone of the representations. With the latter, it became clear to us that the managers do not have a positive social representation to the aspect that pass through their professional act. As well as it has been also possible to confirm the thesis that the contradictions are on the base of the manager’s profession and they guide their work.